IMPLEMENTATION OF STRATEGIC MANAGEMENT IN POVERTY ALLEVIATION: A CASE STUDY OF DUMAI CITY, RIAU - Prayetno, Prayetno; Irvan, Puji Ananda; Nisyah, Habibah Tun; Rineliana, R.; Tampubolon, Omar Farrakhan (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
Purpose: This study analyzes the implementation of strategic management in poverty alleviation efforts in Dumai City, Riau, Indonesia. Poverty in Dumai is a multidimensional issue with unique complexities stemming from its status as an international port city and a center for the oil industry. Methodology: Despite a high Gross Regional Domestic Product (GRDP) per capita, Dumai City's poverty rate remains above the average for urban areas in Riau Province, indicating structural inequality in the distribution of economic development benefits. This qualitative research employed a case study method involving in-depth interviews with 25 key informants, observations, Focus Group Discussions (FGDs), and document analysis. Data analysis utilized a SWOT approach to evaluate internal and external factors influencing program success. Findings: The research results demonstrate a positive correlation between strategic management and the effectiveness of poverty alleviation, with strategy formulation identified as the most influential dimension. Dumai City possesses strong leadership commitment, an integrated information system, institutionalized coordination mechanisms, high community participation, and diversified programs. However, weaknesses include limited institutional capacity, suboptimal operational coordination, a dominance of "charity" approaches, less contextualized strategies, and an output-oriented evaluation system. Opportunities include the city's strategic position, digital transformation, potential for private sector collaboration, tourism development, and the creative economy. Threats are economic dependence on specific sectors, the impacts of climate change, the digital divide, global economic uncertainty, and resistance to change. Implementing strategic management has shown an effect on reducing poverty levels, gaps, and severity, increasing access to basic services and community empowerment. Originality/Value: This study recommends an effective strategic management model through institutional capacity building, adaptive approaches, strengthened collaboration, and an outcome-based evaluation system.